The main concerns of European anaesthesiology postgraduate trainees: A European survey. (February 2018) - Sobreira Fernandes, Diogo; Teixeira, Laetitia; Longrois, Dan; Ateleanu, Bazil; Bornemann-Cimenti, Helmar; Sá Couto, Paula; Kompan, Janez; Rauseo, Michela; Stefan, Mihai; Valeanu, Liana; Matias, Bernardo; Greif, Robert; et al.
Abstract: This is the first study intended to identify the European anaesthesiology trainees' main concerns, to initiate a process of improvement of the training in anaesthesiology by the European Society of Anaesthesiology (ESA). The authors developed an electronic survey which addressed seven different concerns: autonomy transition, technical skills, exchange programs, residency costs, residency workload, employment prospects and educational contents/preparation for the European Diploma in Anaesthesiology and Intensive Care (EDAIC). The survey was disseminated by email to all anaesthesiology trainees registered in ESA and all European National Societies were asked to distribute the survey to their graduating trainees. 665 trainees initiated the survey with a completion rate of 54.6%. The trainees' main concerns were in descending order: educational contents, residency costs, employment prospects, residency workload, exchange programs, technical skills and autonomy transition. This report analyzes the three main concerns in more detail. 68% of respondents were unaware of the existence of the ESA e-learning platform. Other means to improve the preparation for the EDAIC such as a multiple-choice questions book should be developed. The main reason for not becoming an ESA Trainee member was the associated cost and 68% of respondents gave up activities or opportunities during their residency due to economic constraints; 56% of respondents considered emigrating for economic reasons and 28% elected Northern/Central Europe. The results of the present survey may provide additional background information for the development of specific improvements in strategies for training in anaesthesiology. Highlights: To identify the European anaesthesiology trainees' main concerns. Participation of 665 anaesthesia trainees with a completion rate of 56.4%. The 3 main concerns are: education, financial issues and employment prospects. The development of a European trainees' network is a priority. These results can be used by ESA to improve anaesthesia education.